Investigating Best Curriculum, Instruction and Assessment Practices in Exemplary British Schools in UAE - Huzefa, Fatema (2016)
Educators and educational researchers in the UAE, more recently have turned their attention to how to achieve great schools. The schools that are doing good, make sure to keep creating opportunities to maintain their ongoing development, they strive to move on to be outstanding. Similarly the schools that are struggling in making progress need to develop the understanding of what is involved in being successful schools and what are the implications of the criteria used by Dubai School Inspection Bureau (DSIB) in Inspection Framework, to achieve the transformation. The focus of this study is to investigate the implication of three criteria from the DSIB Inspection Framework 2015-16: Curriculum, Teaching and Assessment. Based on the inspection reports British Schools have the highest percentage of achieving outstanding rating among other curricula. So far (at the time of writing), out of 29 very good and outstanding schools 19 schools are offering British Curriculum. The fact that British Curriculum is in close harmony with the DSIB inspections and is able to promote quality education has guided the researcher to select the British schools as samples for the study. In order to investigate the successful implementation of the focused standards in the inspection framework, the researcher included the interviews of the school heads and document analysis to figure out significant features of school organisation and the best practices relating to the standards. This study involved a desk study of school reformation, school development literature, and processes implied in school inspections, also the identification of initiatives by KHDA in order to support schools in their development and the visits to schools, to carry out semi structured interviews. The major results of the study indicated that the success to achieving an effective transformation requires a very strong self-evaluation or self-assessment mechanism in place. The schools should be able to identify the areas for improvement, and based on the priority and urgency level, the leaders develop their school improvement plan around it till they achieve. Another important finding was that external professional support in terms of getting membership of accrediting organisations like BSO and BSME and CIS push successful schools even further to the excellence. Along with inspections, these organisations also provide continuous professional development trainings, so the member schools are now linked with international educational communities. Yet another significant finding indicates that the successful incorporation of external examinations, like GL PTE TIMSS and PISA, allow schools to assess their quality of education in the international perspective therefore the schools are in position to moderate their future policies and actions to support their ongoing development. The progress for the outstanding schools, in major subjects like Mathematics, Science, Reading and Language acquisition, is the rising curve; nevertheless, most of the outstanding schools are in process of developing effective mechanism for better Arabic and Islamic education.